Keberhasilan Keberhasilan Penggunaan Media Pembelajaran Interaktif Berbantuan Software Lectora Inspire dalam Meningkatkan Hasil Belajar Siswa - Isymayati Ash Shiddiqy; I Nyoman Suputra (Universitas Negeri Surabaya, 2022)
This research aims to develop (1) Interactive learning media facilities and infrastructure based on lectora inspire software, (2) Know the feasibility of interactive learning media based on lectora inspire software, and (3) Know the difference in learning outcomes before and after using interactive learning media products based on lectora inspire software in students of class XII OTKP. The subjects in this study are media experts, material experts, and students of class XII OTKP SMK PGRI 6 Malang. Development in this research in the form of learning media products based on the Lectora Inspire Authoring Tool software using research & development (R&D) methods that adapt the development procedures of Borg & Gall which has ten steps of research. The acquisition of data is taken from quantitative and qualitative data. The results of the data analysis showed that 1) Interactive learning media based on lectora inspire software that has been developed showed results worth using based on the percentage of success of media experts, material experts, and users, 2) Interactive learning media on materials implementing security and maintenance of facilities and infrastructure can improve learners' learning outcomes. So the use of learning media based on lectora inspire software is worth and can improve learners' learning outcomes.